IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE TWO STAY TWO STRAY (TS TS) TO INCREASE ACTIVITY AND ACHIEVEMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) STUDENT CLASS X.4 SMA NEGERI 1 SUKASADA - Suprianto, Komang Agus (Universitas Pendidikan Ganesha, 2012)
This research aims to (1 ) increase ICT learning student activities class X.4 SMA Negeri 1 Sukasada through implement model two stay two stray, (2 ) increase ICT student achievement class X.4 SMA Negeri 1 Sukasada through implement model two stay two stray and (3 ) Know student response class X.4 SMA Negeri 1 Sukasada through implement model two stay two stray in ICT learning. This research is Classroom Action Research that consisting of two cycles. Each cycle consists of four stages: action plannings, action performing, observation and evaluation, and reflection. Subjek of this research is student class X.4 SMA Negeri 1 Sukasada school year 2011 / 2012 as much 32 person. while the research object are (1 ) learning student activities, (2 ) Students Achievement and (3 ) student response to ICT learning through two stay two stray model . Data about activity and student achievement student were gathered through testing and observation methods and student response data be gathered through questionnaire. The data collected were analyzed using descriptive analysis. The results of this research indicate that increased student learning outcomes, in the first cycle average learning outcomes and student of classical completeness 76.88 and 75% in the second cycle to be 80.23 and 87.5%, for learning activities on sikus I at 8.25 on a 9.48 second cycle. The results of the analysis of students' response to the application of the two stay two stray learning in teaching ICT was positive with an average score of 39.47.